Landscape Strategies in Architecture - Daniel Jauslin (A+BE: Architecture and the Built Environment)
The central question and purpose of the thesis is to understand how landscape as a design concept is changing our understanding of architecture. It explores the ways in which landscape is relevant for design strategies in architecture.